Development of Science Learning E-Modules Using the Flip PDF Application - Muhammad Rifqi Nugroho; Bambang Sumardjoko; Achmad Fathoni (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the results of the validity and the practicality of science e-modules using the flip pdf application at SMP Muhammadiyah Al-Kautsar PK. Development research was conducted using the ADDIE model. Interviews and questionnaires were used as data collection techniques. The data analysis technique used descriptive qualitative and quantitative analysis. The e-module product validation was carried out by three experts, namely subject content experts, design experts, and media experts, with an average score of 93.3%, indicating that the E-Module was in very good qualification. The practicality test was carried out using a student response questionnaire after using the e-module; an average of 93.7% was obtained with very practical criteria. The conclusion is that the science e-module developed using the flip pdf application is valid and practical.